2010
DOI: 10.1007/s00213-010-1894-8
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline, a dopamine receptor agonist, has an antidepressant-like property and enhances brain-derived neurotrophic factor signaling

Abstract: Cabergoline exerts antidepressant- and anxiolytic-like effects, which may be mediated by potentiation of intracellular signaling of BDNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 62 publications
1
17
0
1
Order By: Relevance
“…Down-stream, cabergoline increases expression and signaling of brain-derived neurotrophic factor (BDNF). BDNF is one of the most important suppressors of food intake, and BDNF is low in PWS (80, 81). …”
Section: Implications Of Ghsr1:drd2 Heteromers In Obsessive Eating Asmentioning
confidence: 99%
“…Down-stream, cabergoline increases expression and signaling of brain-derived neurotrophic factor (BDNF). BDNF is one of the most important suppressors of food intake, and BDNF is low in PWS (80, 81). …”
Section: Implications Of Ghsr1:drd2 Heteromers In Obsessive Eating Asmentioning
confidence: 99%
“…Cabergoline, an ergot derivative that causes delusions , is a dopamine agonist that has an antidepressant-like property [31]. The dopamine receptor agonist pergolide has shown antidepressant effects in Parkinson patients [32].…”
Section: Resultsmentioning
confidence: 99%
“…Neurotrophic factors evoke ERK activation and promote proliferation, differentiation, neurite outgrowth and survival, while stress stimuli induce ERK activation that mediates cell death [38][43]. Here, we first examined whether cabergoline increased the expression of BDNF as we previously reported that upregulation of BDNF in hippocampal tissues by cabergoline [21]. Furthermore, BDNF has neuroprotective effects via the activation of Akt and ERK signaling [38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cabergoline could also affect these brain regions. Indeed, we previously reported that cabergoline increases hippocampal brain-derived neurotrophic factor (BDNF, an important regulator in the synaptic plasticity) and exerts an antidepressant effect in rats [21], [22], suggesting a beneficial effect of cabergoline on neuronal populations other than those in the mesencephalon. In the present study, we investigated the neuroprotective effect of cabergoline against oxidative stress caused by H 2 O 2 in cultured cortical neurons, and found that significant neuroprotection occurred by a D 2 receptor-mediated mechanism.…”
Section: Introductionmentioning
confidence: 99%